2014
DOI: 10.1002/ejlt.201400253
|View full text |Cite
|
Sign up to set email alerts
|

Margarine supplemented with conjugated linolenic acid (CLnA) has no effect on atherosclerosis but alleviates the liver steatosis and affects the expression of lipid metabolism genes in apoE/LDLR‐/‐ mice

Abstract: Margarine supplemented with conjugated linolenic acid (CLnA) has no effect on atherosclerosis but alleviates the liver steatosis and affects the expression of lipid metabolism genes in apoE/LDLR -/-mice The objective of this study was to evaluate the effect of margarine supplemented with punicic acid (cis-9, trans-11,cis-13 C18:3) (CLnA) compared to CLA and linolenic acid (LnA) in apoE/LDLR -/-mice in two independent experiments: LONG (18 weeks) and SHORT (10 weeks). Liver weight was increased in CLA group in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Recent studies reported that laying hens fed with pomegranate seed oil significantly incorporate PunA in egg yolks [ 8 , 74 ]. Another study reported that PunA was successfully incorporated in margarine [ 75 ] and in goat milk of animals fed with a diet supplemented with 12% of pomegranate seed pulp [ 76 ]. A different approach would be the production of enriched food supplements that could be taken up by cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that laying hens fed with pomegranate seed oil significantly incorporate PunA in egg yolks [ 8 , 74 ]. Another study reported that PunA was successfully incorporated in margarine [ 75 ] and in goat milk of animals fed with a diet supplemented with 12% of pomegranate seed pulp [ 76 ]. A different approach would be the production of enriched food supplements that could be taken up by cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the concentration of serum cholesterol was significantly lower in the CLnA than in the linoleic acid group in rats (Koba et al, 2002). In another research, it was found that margarine supplemented with 0.5% CLnA and 0.5% CLA had no significant effect on the TC of mice after short (10 week) and long (18 week) periods of feeding (Franczyk-Zarów et al, 2015). Koba et al, (2002) also demonstrated how 1% CLA exhibited a decreasing trend, although this cholesterol-lowering effect was not statistically significant against 1% linoleic acid.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, this author showed that feeding diets supplemented with 1% purified punicic acid did not exhibit a significant effect on HDL-C in hamsters. Furthermore, it was reported that margarine supplemented with 0.5% punicic acid (cis9, trans11, cis13-18:3), 0.5% CLA and linolenic acid had no effect on HDL-C serum in apoE/LDLR-/-mice after short (10 weeks) and long (18 weeks) periods (Franczyk-Zarów et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6J mice fed a CLAenriched diet developed a state resembling diabetes, with a marked insulin resistance (hyperinsulinemia) [29]. Also, in studies of Halade et al (2010) the fasting serum glucose concentration was significantly increased in CLA-fed mice compared to the Control groups [10].…”
Section: Discussionmentioning
confidence: 97%